Парадигма концепту «смерть» у ліриці О. Тарнавського (екзистенція та коекзистенція) - Василишин, І. (Слово і Час, 2022)
У статті розглянуто парадигму концепту “смерть” у ліриці Остапа
Тарнавського, що є предметом художнього філософування та мистецьких
інтерпретацій українського поета-емігранта. Досліджено, що лірика
О. Тарнавського, у якій висвітлено проблеми людського буття, морально-психологічні аспекти кінцевості земного існування, засвідчує насамперед дуалізм поглядів Тарнавського-мислителя, котрий прагне осягнути
смерть, з одного боку, як кінцевість людського буття-у-світі, що передбачає екзистенційну тривогу й трагічне усвідомлення її незворотності та, врешті, подолання страху смерті для досягнення автентичності існування, а з другого, — як коекзистенцію: співіснування зі смертю — провідником людини на шляху до вічності. The article considers the paradigm of the concept of death in the lyrics by Ostap Tarnavsky
as a subject of his poetic philosophical thinking and interpretations.
O. Tarnavsky’s lyrical poetry, in which the poet highlights the problems of human existence,
moral and psychological aspects of the finiteness of earthly existence, reveals the dualism of the author's thoughts. The poet sought to comprehend death, on the one hand, as the
end of human existence, which implied facing its tragic irreversibility and then overcoming
the fear of death for achieving the authenticity of being. On the other hand, he admitted
coexistence with death, which is the guide of a man on the path to eternity. The philosophical
concept of coexistence as a common being of the human self with others and with the
world was substantiated by the Italian existentialist philosopher Nicola Abbagnano in his
work “Introduzione all'esistenzialismo” (1942). Poetic and philosophical understanding of the concept of death as a transition from
earthly existence to eternity was unfolded by O. Tarnavsky in a wreath of sonnets within
the collection “Life”. In the 11th sonnet “The order of the world creates in the head…” the
author equates death with immortality because only aft er the completion of the earthly path
a person approaching God in life – “perceives the One who creates” and gets Him. In his
poems, O. Tarnavsky comprehends the earthly space and time as a certain section of moving
to eternity and seeks to outline its coordinates (“Phantoms in Emptiness”). DeaThis only a
coexistent form of eternity that changes one stage into another. The situation of birth and
death, according to the Italian philosopher-existentialist N. Abbaniano, is the very depth of
coexistence. In the poem “Where do you call to go, princess?..” the paradigm of the concept
of death is narrowed and existentially personalized to ‘my death’, which eventually transforms
into the author’s vision of death. In his philosophical lyrics, O. Tarnavsky covers the problems of human existence –
earthly and eternal, psycho-spiritual and moral-psychological aspects of the last stage of
earthly life. The poet represents the dialectic of life and death and, in particular, the paradigm
of death, from religious, philosophical, and axiological points of view. At the same
time, he demonstrates purely psychological reflections, expressed in spiritual and emotional experiences.